(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article analyzes the theoretical foundations of psychological services, scientific research conducted by our and foreign scientists, ideas about individual psychological differentiation and theories aimed at understanding and understanding the inner world of a person.